2018
DOI: 10.1016/j.jtemb.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary zinc intake and whole blood zinc concentration in subjects with type 2 diabetes versus healthy subjects: A systematic review, meta-analysis and meta-regression

Abstract: The aim of this systematic review, meta-analysis and meta-regression was to examine the relationship between type 2 diabetes mellitus (T2DM) and concentration of zinc in whole blood, as well as dietary zinc intake. Searches were performed using Ovid MEDLINE, Embase (Ovid) and The Cochrane Library (CENTRAL). Observational studies conducted on diabetic and healthy adults, with data on dietary zinc intake and/or concentration of zinc in whole blood, were selected. The search strategy yielded 11,150 publications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
2
8
1
5
Order By: Relevance
“…Meanwhile, Simic et al [19], did not find a significant relationship in previously diagnosed T2DM patients and control subjects. These results seem to suggest that when T2DM is in the early stages, i.e., newly diagnosed, zinc levels are more elevated than non-diabetic subjects, and progressively they are reduced as the disease progresses, which is consistent with our previous systematic review and meta-analysis [20]. That meta-analysis which aimed to compare whole blood zinc concentration between T2DM patients and non-diabetic subjects, showed that duration of T2DM had a relevant influence on concentration of zinc in whole blood [20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Meanwhile, Simic et al [19], did not find a significant relationship in previously diagnosed T2DM patients and control subjects. These results seem to suggest that when T2DM is in the early stages, i.e., newly diagnosed, zinc levels are more elevated than non-diabetic subjects, and progressively they are reduced as the disease progresses, which is consistent with our previous systematic review and meta-analysis [20]. That meta-analysis which aimed to compare whole blood zinc concentration between T2DM patients and non-diabetic subjects, showed that duration of T2DM had a relevant influence on concentration of zinc in whole blood [20].…”
Section: Discussionsupporting
confidence: 91%
“…These results seem to suggest that when T2DM is in the early stages, i.e., newly diagnosed, zinc levels are more elevated than non-diabetic subjects, and progressively they are reduced as the disease progresses, which is consistent with our previous systematic review and meta-analysis [20]. That meta-analysis which aimed to compare whole blood zinc concentration between T2DM patients and non-diabetic subjects, showed that duration of T2DM had a relevant influence on concentration of zinc in whole blood [20]. In addition, we found a lower whole blood zinc concentration in T2DM patients; however, this group had, at least, 10.2 ± 8.6 years of duration of diabetes, and differences between cases and controls in that study were not observed [58], in concordance with the study of Simic et al [19], among previously diagnosed T2DM participants [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data are comparable to YU-SAD data for adult category, however our data indicate slightly lower intake of zinc within both adolescent groups. A comprehensive systematic review, meta-analyses and meta-regression, demonstrated significantly lower intake of zinc among diabetic patients, only if the condition is with associated co-morbidities (Fernández-Cao et al, 2018). However, blood zinc status was lower in diabetic subjects in comparison with healthy controls, regardless of the complications, indicating necessity for adequate biomarkers of the nutrient intake (Fernández-Cao et al, 2018).…”
Section: G Seleniummentioning
confidence: 99%
“…Peranan transporter zinc yang lain pada fungsi sel β memungkinkan konstribusinya pada tatalaksana hiperglikemi pada pasien diabetes 6 . Konsentrasi zinc secara signifikan lebih rendah pada pasien diabetes dibanding dengan non diabetes 7 . Pasien DM Tipe2 memiliki kadar zinc yang lebih rendah dan hal ini terkait dengan tingginya komplikasi mikrovaskular diabetes 8 .…”
Section: Idfunclassified